(untitled) (Human Factors in Design, 2023)
The present review aimed to analyze the main occupational risk factors associated with telecommuting, as well as their consequences. Another objective was to identify the countries that have been conducting studies on this topic. Twenty-six articles were considered, as they met all the inclusion criteria and were published from 2012 to 2022. The majority of the studies were conducted in Japan (11.5%). Among the risk factors identified in the publications related to telecommuting, the incidence of pain, discomfort, and psychosocial risks stood out. Although studies on psychosocial risks were fewer in number, they provided relevant findings. However, further research is needed to continue and deepen scientific knowledge in this field.